Wellness City Health and Well-being in Urban Economic Development - Anttiroiko, Ari-Veikko (Springer International Publishing, 2018)
'Wellness is a major economic trend of our time. Anttiroiko highlights key dimensions of wellness-oriented policy and reveals empirical cases that illustrate how local governments can profit from wellness strategies. This book should be read by students, experts and public managers looking to create new policies on local economic development.' - Nicos Komninos, Professor, URENIO Research, Aristotle University of Thessaloniki 'Wellness City provides a balanced perspective on how health and well-being relate to the promotion of both economic development and inclusive prosperity. This book provides valuable guidance for policy-makers and scholars who are puzzled by the challenges of urban economic development.' - Hiroyuki Mori, Professor of Economics, Ritsumeikan University Addressing the continuous need for new growth sectors in post-industrial cities, this book considers the economic significance of wellness from a development policy perspective. The author goes beyond personal health discourse to conceptualise wellness as an emerging industry, presenting empirical cases of community, attraction, and export-orientated strategies around the world. Combining holistic health, urban governance and economic development, this book will provide valuable reading for those studying policy, tourism and the wellness sector as well as business entrepreneurs within this evolving industry.